Journal of Human Sport and Exercise - 2020 - Summer Conferences of Sports Science 2020
DOI: 10.14198/jhse.2020.15.proc4.30
|View full text |Cite
|
Sign up to set email alerts
|

Effects of power resistance training program with elastic bands on body composition, muscle strength and physical function in older women

Abstract: The aim of this study was to investigate the effects of a power-strength resistance program with elastic bands on body composition, physical function, and muscle strength in older women. For such purpose, a randomized controlled trial with a pre-post-intervention design was conducted. Thus, 58 healthy, physically independent, sedentary women, aged 65-85 years, were randomly allocated to the intervention (n = 28) or control group (n = 30). Measurements of body composition (total mass, total fat mass, total skel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Recent meta-analysis studies have reported that the RT protocol can moderately increase muscle mass in post-menopausal and elderly women but does not reduce fat mass [ 33 ]. Flandez et al reported that among older women, power resistance training with elastic bands for 20 weeks led to significant negative changes in fat mass, fat-free mass, and body fat percentage in the control group [ 34 ]. These findings are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analysis studies have reported that the RT protocol can moderately increase muscle mass in post-menopausal and elderly women but does not reduce fat mass [ 33 ]. Flandez et al reported that among older women, power resistance training with elastic bands for 20 weeks led to significant negative changes in fat mass, fat-free mass, and body fat percentage in the control group [ 34 ]. These findings are consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Both weight plates (WP) and elastic bands (EB) have been used in resistance training to gain muscle mass and strength in a wide range of populations such as trained athletes and older adults [ 1 , 2 , 3 ]. Indeed, both WP and EB may induce similar strength gains (upper limbs: Standardized Mean Difference [SMD] = −0.11; 95% CI = −0.40, 0.19; p = 0.48; lower limbs: SMD = 0.09; 95% CI = −0.18, 0.35; p = 0.52) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, whether this improvement can provide them with other benefits toward improving their functional and physiological capacities, which can positively affect their health and quality of life, remains unknown (Moors et al,2004;Peterson et al, 2011;Raymond et al, 2013). Elastic bands have emerged as an effective, affordable, portable, and easy-to-maintain alternative material that could be used for training at different intensities to improve muscle strength (Colado et al, 2020a;Flandez et al, 2020;Liao et al, 2018;Martins et al, 2013;Rieping et al, 2019). Moreover, these materials make it possible to easily and effectively control the intensities applied, by combining the number of target repetitions with the width of the grip in a specific band and with the type of effort for specific purpose (Colado et al, 2010;Colado et al, 2014;Colado et al, 2018;Colado et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%